Sala de aula invertida: relato de experiência de tutoria do programa de intercâmbio internacional “Gira Mundo” na Paraíba - Silva, Ketlen Oliveira Estevam da (2017)
In the 21st century, it has observed many available resources that the students can use to improve more and more their knowledge, principally in foreign languages. Immersed in a new reality – now virtual environment, people use digital technologies to interact through social media, they stay connected, they know technologies and applications as anybody else. Then, how to create active learning environments, using activities that work with the students’ daily routine and interest by means of digital technologies? This research aims to report the tutorial experiences developed in the Language Preparatory Course from Gira Mundo International Exchange Programme, using the flipped classroom as methodology in the teaching and learning process in Paraíba’s programme. It has as theoretical foundation Bergmann e Sams (2016), Fino (2008), Paiva (2012), Moran (2012), Bortoni- Ricardo (2008) and other authors. The methodology is based on qualitative research with an ethnographic approach, using not only a questionnaire as data collection instrument to evaluate the preparatory course, but also eight reflexive diaries done by the students. Six of them were written by hand and the others two were typewritten. For this purpose, it was designed a script into two parts to the reflexive diary: the first one related to the students impressions about the programme, and the second part is referred to the evaluation of the teaching and learning process from the classes given by the tutor, through the methodology approaches in 18 classes taught. Furthermore, the activities from Duolingo were guided as recommended by the Exchange programme, and also some activities and postings in a private group created by the students’ tutor in the social medias Facebook and Whatapp to interact, to exchange experiences and extra materials in the English classes. This research concluded that the flipped classroom methodology used by the programme, created active learning environments, with personalized education to the students, and make the teacher/tutor reflect about her pedagogy practice in the classroom.